Development of Learning Devices Two Stay Two Stray Cooperative Model to Increase Social Skills and Learning Outcomes - Fajriyatul Mukhlishina; Wahono Widodo; Nadi Suprapto (Universitas Lampung, 2020)
The purpose of this research is to develop and produce a valid, practical and effective two stay two stray cooperative learning model on the subject of ecosystem the fifth grade elementary school and to describe the results of the implementation of lesson plans, student learning outcomes, social skills, student responses, and the obstacles encountered in implementing learning. This research is conducted in two steps, first is development of cooperative learning models Type Two Stay Two Stray which refers to the four-D development model but until development stage. Second is try learning model that have been developed, in students. The subjects of this study were VA and VB grade students at Ngagelrejo I / 396SDN Surabaya. Testing was conducted using One Group Pretest-Posttest Design. Data collection is done by validation, observation, tests, and student questionnaire responses. The data analysis technique uses descriptive technical analysis. The results of this study indicate that the Two Stay Two Stray cooperative learning model is very valid, practical, and effective for ecosystem material.